2011
DOI: 10.1002/hbm.21381
|View full text |Cite
|
Sign up to set email alerts
|

Seeing with the eyes shut: Neural basis of enhanced imagery following ayahuasca ingestion

Abstract: The hallucinogenic brew Ayahuasca, a rich source of serotonergic agonists and reuptake inhibitors, has been used for ages by Amazonian populations during religious ceremonies. Among all perceptual changes induced by Ayahuasca, the most remarkable are vivid "seeings." During such seeings, users report potent imagery. Using functional magnetic resonance imaging during a closed-eyes imagery task, we found that Ayahuasca produces a robust increase in the activation of several occipital, temporal, and frontal areas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
181
0
4

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 188 publications
(200 citation statements)
references
References 35 publications
15
181
0
4
Order By: Relevance
“…A connectivity analysis revealed that ayahuasca strongly altered fronto-occipital relationships, leading to marked changes in the timing of events across several brain regions. de Araujo et al (2012) speculate that the robust visions induced by ayahuasca may even be initiated in the primary visual cortex.…”
Section: Effects On Visual Perceptionmentioning
confidence: 99%
See 1 more Smart Citation
“…A connectivity analysis revealed that ayahuasca strongly altered fronto-occipital relationships, leading to marked changes in the timing of events across several brain regions. de Araujo et al (2012) speculate that the robust visions induced by ayahuasca may even be initiated in the primary visual cortex.…”
Section: Effects On Visual Perceptionmentioning
confidence: 99%
“…de Araujo et al (2012) investigated the neural basis of imagery induced by the psychedelic Amazonian brew ayahuasca. They studied 10 regular ayahuasca users who participated in two fMRI sessions.…”
Section: Effects On Visual Perceptionmentioning
confidence: 99%
“…These brain areas are involved in the modulation of emotions, internal feelings and sensations, perception and self-awareness. An fMRI study using an imagery task showed that ayahuasca not only increased activation of the parahippocampal and frontopolar cortices, but also of the cuneus and lingual gyrus and retrosplenial cortex 20 . Interestingly, during the imagery task ayahuasca increased activation of the primary visual area in a manner similar to the activation levels of seeing a natural image with the eyes open.…”
Section: Botany Chemistry and Mechanism Of Actionmentioning
confidence: 99%
“…It has been emphasized that the size of the neuroaxonal network makes it ineligible for maintaining this kind of interaction; rather, we should be looking for a subcellular system possibly at the level of the lipoprotein membrane structures-or else (e.g., cytosol) at the bottom of 4 'Perceptual-cognitive' in our use strictly refers to a sensory input driven cognitive processing. Visions can be sensed as profoundly perceptual while lacking the activation of the sensory organs (de Araujo et al, 2012). As we will point out later, veridical information accessed during visionary experiences emerges via the "nonlocalintuitive" channel.…”
Section: Nonlocal Realism and The Second Foundation Of Knowledgementioning
confidence: 99%